Hypoxic Respiratory Chemoreflex Control in Young Trained Swimmers - Arce-Álvarez, Alexis; Veliz, Carlos; Vazquez-Muñoz, Manuel; von Igel, Magdalena; Alvares, Cristian; Ramirez-Campillo, Rodrigo; Izquierdo, Mikel; Millet, Gregoire P.; Del Rio, Rodrigo; Andrade, David C. (Frontiers in Physiology, 2021)
During an apnea, changes in PaO2 activate peripheral chemoreceptors to increase respiratory drive. Athletes with continuous apnea, such as breath-hold divers, have shown a decrease in hypoxic ventilatory response (HVR), which could explain the long apnea times; however, this has not been studied in swimmers. We hypothesize that the long periods of voluntary apnea in swimmers is related to a decreased HVR. Therefore, we sought to determine the HVR and cardiovascular adjustments during a maximum voluntary apnea in young-trained swimmers. In fifteen trained swimmers and twenty-seven controls we studied minute ventilation (VE), arterial saturation (SpO2), heart rate (HR) and autonomic response (through heart rate variability (HRV analysis), during acute chemoreflex activation (five inhalations of pure N2) and maximum voluntary apnea test. In apnea tests, the maximum voluntary apnea time and the end-apnea HR were higher in swimmers than in controls (p<0.05), as well as a higher low frequency component of HRV (p<0.05), than controls. Swimmers showed lower HVR than controls (p<0.01) without differences in cardiac hypoxic response (CHR). We conclude that swimmers had a reduced HVR response and greater maximal voluntary apnea duration, probably due to decreased HVR.